Peak-locking error reduction by birefringent optical diffusers - Kislaya, Ankur; Sciacchitano, Andrea (Measurement science & technology, 2018)
The use of optical diffusers for the reduction of peak-locking errors in particle image velocimetry is investigated. The working principle of the optical diffusers is based on the concept of birefringence, where the incoming rays are subject to different deflections depending on the light direction and polarization. The performances of the diffusers are assessed via wind tunnel measurements in uniform flow and wall-bounded turbulence. Comparison with best-practice image defocusing is also conducted. It is found that the optical diffusers yield an increase of the particle image diameter up to 10 µm in the sensor plane. Comparison with reference measurements showed a reduction of both random and systematic errors by a factor of 3, even at low imaging signal-to-noise ratio.